Noise reduction in phase maps from digital holographic microscopy (2020)
Digital Holographic Microscopy (DHM) is a technique that has allowed the quantitative measurement of the phase delays that microscopic samples introduce into a coherent illumination. The technique, however, suffers from the presence of coherent noise; this deleterious effect of coherent illumination has detrimental results for the resolution power and accuracy of the measured information, hindering the widespread adoption of DHM-based technologies. Therefore, the advancement of DHM and its effective implementation in Quantitative Phase Imaging applications is highly linked to the development of robust denoising methods that can adequately compensate for this limitation. In this Master’s thesis, the proposal and implementation of noise reduction strategies that can be applied to quantitative phase maps numerically obtained from Digital Holographic Microscopy are sought. To achieve so, a review of the state-of-the-art in existing phase-map denoising methodologies was done, finding that, while extensive literature sources that tackle the problem of noise in digital holography exist, most are focused on intensity information; meanwhile, the few that are optimized for phase denoising have been mostly used in macroscopic objects thus failing to consider the experimental conditions of DHM. Under this understanding, new denoising methodologies adapted to the specific experimental conditions of DHM are explored, its feasibility verified on both numerically modeled and experimental results, and their application limits established with previously reported metrics from the existing literature. The results were reported on 9 manuscripts submitted to indexed journals of international circulation, 7 of them already published, and 6 presentations in international conferences. These products constitute the core of the present thesis.